Financial toxicities of cancer in low‐ and middle‐income countries: Perspectives from Southeast Asia. Issue 16 (17th June 2022) - Eala, Michelle Ann B.; Dee, Edward Christopher; Ginsburg, Ophira; Chua, Melvin Lee Kiang; Bhoo‐Pathy, Nirmala
Abstract : This commentary draws attention to the financial toxicities associated with cancer in low‐ and middle‐income countries from the perspective of Southeast Asia. It describes interventions at patient–provider, hospital, health care system, and national levels that may mitigate financial toxicity in the region and in similarly resourced parts of the world.